Using Canva Application as a Learning Innovation In Improving Students' Narrative Text Writing Ability XI Grade TEI 2 SMKN 3 Kendal - Pris Setyanti, Siska; Aimah, Siti (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
The increasingly rapid development of information technology in the current era of globalization is having a very strong influence on the world of education. Global demands require the world of education to always adapt to technological developments to improve the quality of education. Teachers are an important component in the learning process. The teacher's spirit of professionalism and creativity will be able to improve the learning process  so as to improve the quality of education. To make all this happen, concrete things are needed so that the quality of learning is even better. Based on initial observations, there are still problems in improving the quality of learning, such as the lack of awareness or motivation of students to learn English, especially narrative text material. Teachers and students are used to conventional learning methods (experimental research) and feel comfortable with this way of learning so they don't feel confident in trying new methods in innovative learning, especially those based on technology. Several literature studies explain that the use of various media, including internet technology-based applications, has now supported increased student learning. including the use of canva application for learning which has a significant impact on students. By using canva application, the learning process is not boring, teachers can teach with creativity, and teach skills to students. This is in accordance with the findings of (Garris Pelangi, 2020) and (Yundayani et al., 2019), who found that the learning strategy of using Canva for education allows students to gain a better understanding and mastery of subject matter, thereby helping students to personalize their learning experience. they. Next, according to the findings of Fauziyah, Widodo, and Yappi, students' perceptions of using Canva in class had a lot of impact on improving their writing skills and they felt enthusiastic about learning using canva for education application (Fauziyah, Widodo, Yappi: 2022). The following findings show that through Canva educators are able to design teaching presentations as well as make recordings. This can help educators to increase digital literacy and teaching creativity for students (Maolida and Salsabila, 2021). canva application can be used in the educational realm, even during the current independent curriculum era.